Yield of winter wheat depending on precursors, fertilizers and liming - L. N. Prokina; S. V. Pugaev (Аграрная наука Евро-Северо-Востока)
The research was aimed at comparing the characteristics of winter wheat precursors on leached heavy loam chernozem in the conditions of the Republic of Mordovia. The object of the study was winter wheat of the Mironovskaya 808 variety, grown in grain-grass-fallow-row (1996-1997) and grain-grass-row (2008-2009) crop rotations, where the precursors were pure fallow and lucerne grass of the 3d year of use. In the control variant (without lime and mineral fertilizers), the crop yield after pure fallow was 3.27 t/ha, after perennial grasses it was 3.72 t/ha. Liming of the soil introduced in 1989-1990 and 1999-2000 did not make significant changes in crop yield, but the combined action with fertilizers in the grain-grass-fallow-row crop rotation against the background of liming by 1.0 h. a. contributed to a greater increase (0.43 t/ha) than against the background of liming by 0.5 h. a. (0.28 t/ha). In grain-grass-row crop rotation, on the contrary, against the background of liming by 0.5 h. a, more grain was obtained (0.74 t/ha), than against the background of 1.0 h. a (0.51 t/ha). The effect of fertilizers without lime was estimated by a less increase in yield ‒ 0.36 and 0.78 t/ha, respectively by crop rotations. Taking into account the payback of 1 kg a.i. of mineral fertilizers with an additional grain yield and additional income, the following doses can be recommended in addition to phosphorus-potassium: the use of nitrogen fertilizer in the top-dressing in the following doses: in the grain-fallow-grass-row crop rotation not more than 30 kg a. i., in grain-grass-row ‒ 30-60 kg a.i. against the background of soil liming by 0.5 h. a.